Resource Mobilization by Indian Mutual Fund Industry - Viramgami, Hitesh S. (Indian Journal of Finance, 2009)
Mutual funds have come as a boon to the small and medium investors and they have emerged as the popular media through which small and medium investors can reap the benefits of good investing. There is no other safe way to enter in the capital market, except the mutual funds. Mutual fund is a specific type of investment institution, which collects the savings of the community and invests large funds in a fairly large and well diversified portfolio of sound investments. It is set-up in the form of a trust. Mutual funds are the vehicles through which savings from individuals are mobilized to the capital market. With the emerge of mutual funds; a change is taking place in the composition of investors. The traditional investors, who used to invest in mutual funds, keeping in view the college education for children and retirement age, are giving way to youngest generation with shorter time horizon and greater expectations. The realization that no single investment product could meet all the financial needs of investors, had led the mutual funds to develop a wide variety of products. In the present paper, an attempt has been made to analyze total resource mobilization by the mutual funds for last eight years from March 2000 to March 20007 and to calculate growth rate to show trends in total resource mobilization. The analysis of the data indicates that Gild, Income and Liquid/MM schemes have shown significant growth, in terms of resources mobilization, Liquid/MM, Growth and Income funds have emerged as the most popular schemes among the investors and among various sectors operating in mutual funds, private sector mutual funds have become the most prominent players.